2021
DOI: 10.1055/s-0040-1722187
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Membrane-Bound Models of Coagulation Factors by Combined Experimental and Computational Approaches

Abstract: In the life sciences, including hemostasis and thrombosis, methods of structural biology have become indispensable tools for shedding light on underlying mechanisms that govern complex biological processes. Advancements of the relatively young field of computational biology have matured to a point where it is increasingly recognized as trustworthy and useful, in part due to their high space–time resolution that is unparalleled by most experimental techniques to date. In concert with biochemical and biophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 148 publications
(270 reference statements)
0
3
0
Order By: Relevance
“…The established binding seems equivalent to that suggested in the “Martinsried-1999” model [ 27 ] based on the X-tal structure of FV-C2, the “Milano-2006” model [ 28 ] based on FV-C2 bound to PE membrane, the “Rochester-2013” model [ 39 ] with a significantly slanted FVIIIa measured by FRET, and the “Måløv-2015” model [ 33 ] from molecular dynamics simulation (we adopt the model notation of our recent review article, Ref. [ 36 ]). The predicted hydrogen-bond interactions inside the major PS-binding site of the “Martinsried-1999” model [ 27 ] (Fig 5A in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The established binding seems equivalent to that suggested in the “Martinsried-1999” model [ 27 ] based on the X-tal structure of FV-C2, the “Milano-2006” model [ 28 ] based on FV-C2 bound to PE membrane, the “Rochester-2013” model [ 39 ] with a significantly slanted FVIIIa measured by FRET, and the “Måløv-2015” model [ 33 ] from molecular dynamics simulation (we adopt the model notation of our recent review article, Ref. [ 36 ]). The predicted hydrogen-bond interactions inside the major PS-binding site of the “Martinsried-1999” model [ 27 ] (Fig 5A in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 In addition, the membrane environment may likely play a role in affecting the protein localization, molecular orientation, and functions through various mechanisms (e.g., by an allosteric effect). 53,55,56 Indeed, it has been shown that phospholipids and the detergent Triton X-100 can increase the activity of truncated SpsB lacking TMD. 57,58 We therefore explored the TMD interaction with the membrane, protein's domain-domain bending in the membrane, known to have functional consequences for some proteins, 59,60 as well as the detailed interaction between the ECD and the membrane.…”
Section: Detailed Membrane Interaction and Membrane-bound Orientationmentioning
confidence: 99%
“…2 Computational simulation techniques such as molecular dynamics (MD) are increasingly trustworthy and useful in studying membrane proteins, in part due to their high space-time resolution. [3][4][5][6] However, using MD simulations at atomic resolution or near-atomic resolution (e.g., united atom 7,8 or MARTINI models 9 ) to simulate cellular processes involving membrane proteins at micron scale that occur extremely slowly (compared to the integration time step, which is typically a couple of femtoseconds) has not generally been feasible. Highly coarse-grained (CG) approaches, where significantly more than 4 heavy atoms and associated hydrogens maps into a single CG bead (approximately the MARTINI model resolution 9 ), is one way to overcome limitations of scale when the atomistic detail is less relevant to the question under investigation.…”
Section: Introductionmentioning
confidence: 99%